Enantioselective Total Synthesis of (−)-Acylfulvene and (−)-Irofulven - Siegel, Dustin S. (2009)
[Image: see text] We report our full account of the enantioselective total synthesis of (−)-acylfulvene (1) and (−)-irofulven (2), which features metathesis reactions for the rapid assembly of the molecular framework of these antitumor agents. We discuss (1) the application of an Evans’ Cu-catalyzed aldol addition reaction using a strained cyclopropyl ketenethioacetal, (2) an efficient enyne ring-closing metathesis (EYRCM) cascade reaction in a challenging setting, (3) the reagent IPNBSH for a late stage reductive allylic transposition reaction, and (4) the final RCM/dehydrogenation sequence for the formation of (−)-acylfulvene (1) and (−)-irofulven (2).